Kinetics of the Formation and Dissociation of Gas Hydrates from CO2-CH4 Mixtures - Kristine Horvat; Prasad Kerkar; Keith Jones; Devinder Mahajan (Energies, 2012)
Sequestration of carbon dioxide (CO2) in the form of its hydrates in natural methane (CH4) hydrate reservoirs, via CO2/CH4 exchange, is an attractive pathway that also yields valuable CH4 gas as product. In this paper, we describe a macroscale experiment to form CO2 and CH4-CO2 hydrates, under seafloor-mimic conditions, in a vessel fitted with glass windows that provides visualization of hydrates throughout formation and dissociation processes. Time resolved pressure and temperature data as well as images of hydrates are presented. Quantitative gas conversions with pure CO2, calculated from gas chromatographic measurements yielded values that range from 23 – 59% that correspond to the extent of formed hydrates. In CH4-rich CH4-CO2 mixed gas systems, CH4 hydrates were found to form preferentially.